Granulocyte colony-stimulating factor use in a large British hospital: comparison with published experience - Pérez Velasco R (Centro de Investigaciones y Publicaciones Farmaceuticas, 2010)
Granulocyte colony-stimulating factors (G-CSF) are high-cost agents recommended as prophylaxis of febrile neutropenia or as adjunctive treatment of severe neutropenic sepsis. Their use in high-risk situations such as acute myeloid leukaemia, acute lymphocytic leukaemia, myelodysplastic syndrome and stem cell transplantation is also indicated. Objective: This audit assessed the use of G-CSF within the Oncology and Haematology Service Delivery Unit at Guy's and St. Thomas' hospital (London, United Kingdom).Methods: Patients who received G-CSF in April-May 2008 were identified retrospectively from the pharmacy labelling system, and chemotherapy front sheets, clinic letters and transplantation protocols were reviewed. Patients on lenograstim, in clinical trials or under non-approved chemotherapy protocols were excluded.Results: A total of 104 G-CSF treatments were assessed. The most commonly treated malignancy was breast cancer (41.3%), with docetaxel 100 mg/m2 (34.6%) being the most frequent chemotherapy regimen. The chemotherapy intent was curative in 66.3 % of cases. Pegfilgrastim was used in 73.1 % of cases and primary prophylaxis was the most common indication (54.8%). Stem cell transplantation was the first indication to meet the audit criterion (93.3%), followed by primary prophylaxis (89.5%). There was a considerable non-adherence for secondary prophylaxis (6.7%).Conclusion: The overall level of compliance with the audit criteria was 72.1%. The results for primary and secondary prophylaxis would have been different if FEC100 (fluorouracil, epirubicin, cyclophosphamide) and docetaxel 100 mg/m2 had been considered a single chemotherapy regimen. Also, the lack of access to medical notes may have affected the reliability of the results for 'therapeutic' use.